A prospective study of serum metabolites and colorectal cancer risk. Issue 19 (3rd June 2014) - Cross, Amanda J.; Moore, Steven C.; Boca, Simina; Huang, Wen‐Yi; Xiong, Xiaoqin; Stolzenberg‐Solomon, Rachael; Sinha, Rashmi; Sampson, Joshua N.
Abstract : BACKGROUND: Colorectal cancer is highly prevalent, and the vast majority of cases are thought to be sporadic, although few risk factors have been identified. Using metabolomics technology, our aim was to identify biomarkers prospectively associated with colorectal cancer. METHODS: This study included 254 incident colorectal cancers and 254 matched controls nested in the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial. Serum samples were collected at baseline, and the mean length of follow‐up was 8 years. Serum metabolites were analyzed by ultra‐high performance liquid‐phase chromatography with tandem mass spectrometry, and gas chromatography coupled with mass spectrometry. Conditional logistic regression was used to calculate odds ratios (OR) and 95% confidence intervals (CI) for metabolites above the limit of detection and present in at least 80% of participants. RESULTS: A total of 676 serum metabolites were measured; of these, 447 were of known identity and 278 of these were present in >80% of individuals. Overall, there was no association between serum metabolites and colorectal cancer; however, some suggestive associations were observed between individual metabolites and colorectal cancer but none reached statistical significance after Bonferroni correction for multiple comparisons. For example, leucyl‐leucine was inversely associated (OR comparing the 90th to the 10th percentile = 0.50; 95% CI = 0.32‐0.80; P = .003). In sex‐stratified analyses, serum glycochenodeoxycholate was positively associated with colorectal cancer among women (OR90th vs.10th percentile = 5.34; 95% CI = 2.09‐13.68; P = .0001). CONCLUSIONS: No overall associations were observed between serum metabolites and colorectal cancer, but serum glycochenodeoxycholate, a bile acid metabolite, was positively associated with colorectal cancer among women. Cancer 2014;120:3049–3057. © 2014 American Cancer Society . Abstract : This is the first agnostic metabolomics study with prospectively collected serum to investigate metabolite biomarkers in relation to incident colorectal cancer. Glycochenodeoxycholate, a bile acid metabolite in serum, was associated with a more than 5‐fold increased risk of incident colorectal cancer among women.